Pengaruh Metode Pembelajaran Inquiry Pictorial Riddle Terhadap Hasil Belajar Fisika Pada Sekolah Menengah Atas Negeri 85 Jakarta - Purwono Subagiyadi; Yoga Budi Bhakti; Neng Nenden Mulyaningsih (Navigation Physics : Journal of Physics Education, 2020)
Many factors influence the outcome of learning physics. One factor is considered to be very important is the learning methods and early skills of learners. Then this research aims to know the influence of the method of enquiries pictorial Riddle and Inquiry learning method of learning results of physics by controlling the initial ability of learners in class X IPA SMAN 85 Jakarta. The research methods used are experimental methods with ANAKOVA analysis.  The samples used were students of the X IPA class as many as 72 students spread in X IPA Class 1 and X IPA 2. The research Data used to test hypotheses comes from the daily value document of the results of physics learning outcomes at Law Newton. The instruments used in the test have passed validity tests, reliability, difficulty levels, and differentiation power. From the results of the study came the conclusion that by controlling/controlling the influence of the original ability, there are significant differences in physics learning outcomes among learners who use the Methods enquiries Pictorial riddle (Fcount < ftable = 0.88 < 3.28) and Learning method of inquiry (Fcount < ftable = 0.65 < 3.28).